Oral health-related quality of life before and after crown therapy in young patients with amelogenesis imperfecta. Issue 1 (December 2015) - Pousette Lundgren, Gunilla; Karsten, Agneta; Dahllöf, Göran
Abstract Background Amelogenesis imperfecta (AI) is a rare, genetically determined defect in enamel mineralization associated with poor esthetics and dental sensitivity. Because the condition is associated with negative social outcomes, this study evaluated oral health-related quality of life (OHRQoL), dental fear, and dental beliefs before and after early prosthetic crown therapy for AI during adolescence. Methods The study included 69 patients with AI, aged 6–25 yr: 33 males and 36 females (mean age 14.5 ± 4.3); healthy controls (n = 80), patients with cleft lip and palate (CLP; n = 30), and patients with molar incisor hypomineralization (MIH; n = 39). All matched in age and gender, and all but the CLP group insocioeconomic area. Patients completed three questionnaires measuring OHRQoL (OHIP-14), dental fear (CFSS-DS), and dental beliefs (DBS-R). Twenty-six patients with severe AI between ages 9 and 22 yr received crown therapy and completed the questionnaires twice: before and after therapy. Results OHIP-14 scores were significantly higher among patients with AI (7.0 ± 6.7), MIH (6.8 ± 7.6) and CLP (13.6 ± 12.1) than healthy controls (1.4 ± 2.4) (p < 0.001). After crown therapy, quality of life problems in the 26 patients with severe AI decreased significantly, from 7.8 ± 6.1 to 3.0 ± 4.8 (p < 0.001). Early prosthetic therapy did not increase dental fear or negative attitudes toward dental treatment. Conclusions OHRQoL increased after early crown therapy in patients with severe AI. Therapy did not increase dental fear or negative attitudes toward dental treatment.